The Potentiality of Herbal Remedies in Primary Sclerosing Cholangitis: From In Vitro to Clinical Studies - Elisa Ceccherini; Antonella Cecchettini; Antonella Cecchettini; Maria Aurora Morales; Silvia Rocchiccioli (Frontiers Media S.A., 2020)
Primary sclerosing cholangitis is a complex pathological condition, characterized by chronic inflammation and fibrosis of the biliary epithelium. Without proper clinical management, progressive bile ducts and liver damage lead to cirrhosis and, ultimately, to liver failure. The known limited role of current drugs for treating this cholangiopathy has driven researchers to assess alternative therapeutic options. Some herbal remedies and their phytochemicals have shown anti-fibrotic properties in different experimental models of hepatic diseases and, occasionally, in clinical trials in primary sclerosing cholangitis patients; however their mechanism of action is not completely understood. This review briefly examines relevant studies focusing on the potential anti-fibrotic properties of Silybum marianum, Curcuma longa, Salvia miltiorrhiza, and quercetin. Each natural product is individually reviewed and the possible mechanisms of action discussed.